(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Many electrical and electronic equipment used in homes requires multiple DC and AC power supplies. Existing hybrid converters used in nanogrid systems provide only single AC and DC outputs for single DC input. They also have limitations such as the shoot-through problem and the requirement of dead time circuitry. This paper proposes a novel Single Input Multiple Output Hybrid Converter (SIMOHC) derived from the DC-DC boost converter, which can produce one AC and two DC outputs simultaneously in a single stage from a single DC input with the less complex circuit. The proposed converter has higher Electromagnetic Interference (EMI) immunity, no shoot-through problem, and dead time circuitry requirement is avoided. The proposed converter uses simple Unipolar Sinusoidal Pulse Width Modulation (USPWM) technique and provides higher reliability. The proposed converter is validated using simulation and hardware implementation. It is observed that the proposed circuit performs equally well compared to the existing hybrid converter like Boost Derived Hybrid Converter (BDHC), and in addition, has the advantage of providing two DC outputs and one AC output.